How Much is the Cathedral of St. Isaac of Dalmatia and Why a Struggle for Possession of the Property? - Alexander Nickolaevich Tsatsulin (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article discusses main problems of of preservation of cultural heritage of St. Petersburg included in the List of monuments of federal significance, that guard UN programs. Raised issues of recovery, restoration, protection and professional assessment of the value of real estate, in particular, the example of the city’s Cathedral of St. Isaac’s Cathedral. The connecting node in the article raised issues and questions turned out to be the subject of a dispute with the Russian Orthodox Church on the ownership of urban real estate.